How Do We Get Paid for This? The Relationship Between Strategic Design Management and Pricing Power - Ian D. Parkman (Cubic Journal)
The belief that strategic design leads to improved firm competitiveness is broadly recognised in contemporary research. However, much less is understood about the precise, concrete mechanisms by which organizations translate their design-based resources and capabilities into higher performance. This paper provides context to this relationship by introducing the variable of pricing power as a potential element of unobserved “dark matter” that clarifies how design-based differentiation results in product performance. Pricing power is described by Stephan Liozu (2019) as “the ability to increase prices without losing demand”. Remarkably, nowhere in the vast literature on pricing is design mentioned, while in parallel pricing has not appeared to be of particular interest to strategic design researchers. In an effort to spur further interest in this variable a case study is provided, illustrating the process footwear and apparel brand Nike employed to leverage design-based differentiation to support the pricing power of a new offering.